Decreased Axial Diffusivity within Language Connections: A Possible Biomarker of Schizophrenia Risk - Kubicki, M (2013)
Siblings of patients diagnosed with schizophrenia are at elevated risk for developing this disorder. The nature of such risk associated with brain abnormalities, and whether such abnormalities are similar to those observed in schizophrenia, remain unclear. Deficits in language processing are frequently reported in increased risk populations. Interestingly, white matter pathology involving fronto-temporal language pathways, including Arcuate Fasciculus (AF), Uncinate Fasciculus (UF), and Inferior Occipitofrontal Fasciculus (IOFF), are frequently reported in schizophrenia. In this study, high spatial and directional resolution diffusion MRI data was obtained on a 3T magnet from 33 subjects with increased familial risk for developing schizophrenia, and 28 control subjects. Diffusion Tractography was performed to measure white matter integrity within AF, UF, and IOFF. To understand these abnormalities, Fractional anisotropy (FA, a measure of tract integrity) and Trace (a measure of overall diffusion), were combined with more specific measures of axial diffusivity (AX, a putative measure of axonal integrity) and radial diffusivity (RD, a putative measure of myelin integrity). Results revealed a significant decrease in Trace within IOFF, and a significant decrease in AX in all tracts. FA and RD anomalies, frequently reported in schizophrenia, were not observed. Moreover, AX group effect was modulated by age, with increased risk subjects demonstrating a deviation from normal maturation trajectory. Findings suggest that familial risk for schizophrenia may be associated with abnormalities in axonal rather than myelin integrity, and possibly associated with disruptions in normal brain maturation. AX should be considered a possible biomarker of risk for developing schizophrenia.